Hubungan Motivasi Belajar, Pemanfaatan Media Teknologi Informasi, dan Komunikasi Pembelajaran Terhadap Pencapaian Pembelajaran IPA - M.A. Santika; I.N. Natajaya; I.M. Yudana (Jurnal Administrasi Pendidikan Indonesia, 2021)
The study was conducted in order to investigate the relationship between students' learning motivation and the use of information and communication technology media in science learning on the Science Learning Outcomes of Class IV Students at the Elementary School Cluster II Kuta. The present research was an ex post facto research. There were 262 people who became the population in this study. The research sample was taken randomly, amounting to 78 people. Collecting data using learning outcomes tests to obtain data on learning outcomes and questionnaires on motivation and use of ICT media to obtain data on student learning motivation and data on the use of ICT media. The data analysis technique used ANAREG. The results showed that: (a) there was a significant relationship between learning motivation and science learning outcomes for fourth graders of SD Cluster II Kuta for the 2020/2021 academic year, which was 15% with rxly = 0.38; (b) there is a significant relationship between entrepreneurs using ICT media and science learning outcomes for fourth grade students of SD Cluster II Kuta for the 2020/2021 academic year, which is 53% with rx2y = 0.72; (c) A significant relationship between learning motivation and the use of ICT media with the learning outcomes of fourth graders of SD Cluster II Kuta for the 2020/2021 academic year, which is 68% with rx2y = 0.82 was found..